PETROGENESA BATUAN DIORIT PADA FORMASI DIORIT LEMBAI DESASNAIMBOY, KECAMATAN WARMARE, KABUPATEN MANOKWARI, PROVINSI PAPUA BARAT - Philipus Samuel (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2023)
Desa Snaimboy and it’s surroundings are a neolithic rock composed of diorite and localized gabbro (Pieters et al., 1990; Webb et al., 2020), which are widespread and form small mounds to the mountains. It is dominated by Tertiary intrusive igneous rocks. The purpose of this study is to analyze the characteristics and petrogenesis of diorite rocks in the Lembai Diorite Formation in the study area. Analysis that can describe the characteristics of lithology and the origin of rock formation is by carrying out petrological analysis and petrographic analysis. The results of the petrological analysis show that the diorite in the Lembai Diorite Formation has a characteristic weathered color of brownish black and fresh black color with white spots. Granularity in general is faneric – porphyritic, euhedral – subhedral crystal form, holocrystalline – hypocrystalline crystallinity, with coarse – very coarse crystal size, and inequigranular crystal uniformity. The structure is generally massive. The mineral composition of diorite is composed of 5-10% quartz, 50-60% plagioclase, 10-20% k-feldspar, 30-40% hornblend, 1-3% biotite, 10-20% pyroxene (Travis, 1975). The results of petrographic analysis show that the diorite in the Lembai Diorite Formation mainly consists of syenogranite and monzogranite. The type of magma formation is peraluminous or MPG (Muscovit-bearing Peraluminous Granite) type (Barbarin, 1999).